HRM and the health of hospitals. (May 2019) - Wilkinson, Adrian; Muurlink, Olav; Awan, Nabil; Townsend, Keith
While there is a plethora of research on people management and high-commitment management, most are focused on commercial enterprises. Even the high-commitment management literature on commercial organisations argues that we need to move beyond the confines of financial performance. There are relatively few studies of high-commitment management which focus on hospitals. This is despite the fact that human resources are a major cost and source of performance leverage in hospitals.